Peer Social Support Enhances a Student's Motivation to Engage in Studying - Najmi Hayati; Muhamad Ismail; Pardi Zukri (CV Najmi Edu Creative, 2025)
This study was carried out at SMPS IT AL-HUSNA, located in the Siak Hulu district of Kampar, Indonesia. The research focused on students in the ninth grade and aimed to examine the impact of peer social support on students' willingness to learn. This research employs a quantitative strategy utilising the correlation approach. A questionnaire was distributed to 120 students to gather responses. Some students continue to experience a lack of social engagement with their peers, leading to feelings of loneliness and isolation. This generates a perception of disparity among classmates, which has a negative impact on the student's motivation to learn, leading to a decrease in their learning drive. The decline in motivation serves as a significant indicator for the necessity of fostering peer-to-peer comprehension in order to effectively engage in interactions both within and beyond the classroom, encompassing intellectual, social, and behavioural aspects. Enable the instructor to offer assistance in promoting comprehension, as well as implementing strategies to enhance peer involvement, motivation, and opportunities for future student achievement. Descriptive statistical analysis is employed to characterise respondent profiles and address research inquiries by quantifying the mean and standard deviations. The determination coefficient value of 78% demonstrates a substantial influence of peer social support on student learning motivation. It signifies that as the level of social assistance from peers rises, the level of motivation among pupils to acquire knowledge would also increase. Facilitating teachers in fostering peer-to-peer engagement through interactive activities among students will enhance motivation in classroom learning.